The loss rates of web tags applied to day-old Anas and Aythya ducklings - Blums, Peter; Mednis, Aivars; Bauga, Ilmars; Nichols, James D; Hines, James E (Wildfowl, 1996)
We double-marked 4,569 day-old ducklings of five species with web tags and plasticine-filled rings in 1991 and studied tag loss over 3-month, 1-year, 2-year and 3-year periods. The web tag loss for Anas was higher than that for Aythya and occurred primarily during the 3-month period following marking. Loss rates after this period were low and could not be distinguished between the two genera. Higher loss rates for Anas v Aythya might be explained by differences in web durability and duckling behaviour during the early posthatch period. We recommend that plasticine-filled rings (Blums et al. 1994) be used in place of web tags because these rings have high retention rates, greater visibility to hunters and permit additional inferences about duckling survival rates.